Bioengineered constructs combined with exercise enhance stem cell-mediated treatment of volumetric muscle loss - Quarta, Marco; Cromie, Melinda; Chacon, Robert; Blonigan, Justin; Garcia, Victor; Akimenko, Igor; Hamer, Mark; Paine, Patrick; Stok, Merel; Shrager, Joseph B.; Rando, Thomas A. (Nature communications, 2017)
Volumetric muscle loss (VML) is associated with loss of skeletal muscle function, and current treatments show limited efficacy. Here we show that bioconstructs suffused with genetically-labelled muscle stem cells (MuSCs) and other muscle resident cells (MRCs) are effective to treat VML injuries in mice. Imaging of bioconstructs implanted in damaged muscles indicates MuSCs survival and growth, and ex vivo analyses show force restoration of treated muscles. Histological analysis highlights myofibre formation, neovascularisation, but insufficient innervation. Both innervation and in vivo force production are enhanced when implantation of bioconstructs is followed by an exercise regimen. Significant improvements are also observed when bioconstructs are used to treat chronic VML injury models. Finally, we demonstrate that bioconstructs made with human MuSCs and MRCs can generate functional muscle tissue in our VML model. These data suggest that stem cell-based therapies aimed to engineer tissue in vivo may be effective to treat acute and chronic VML. Volumetric muscle loss leads to functional muscle impairment, and current stem cell-based treatments show limited efficacy. Here, the authors generate a stem cell scaffold, implant it in mice, and show that an exercise regimen enhances innervation and restoration of muscle function in mice.